The modelling of emissions evaluation at asphalt mixing plant in hot recycling - Martišius, Mindaugas; Sivilevičius, Henrikas (Transport, 2022)
Transport industry with its infrastructure sector is one the main sources of GreenHouse Gas (GHG) emissions. In parallel, this industry has the main part on gross domestic product of a high transport transit countries with a develop road network. Transport infrastructure (TI) must be continuously developed, improved, and carefully maintained accordingly traffic and goods flow with respect to safety and emissions. Renewable resources, such as Reclaimed Asphalt Pavement (RAP) and energy from sustainable sources are the main accents reducing carbon emissions in the industry. The comparison outlook of different technologies emissions in a Hot-Mix Asphalt (HMA) with RAP production at Asphalt Mixing Plant (AMP) are presented in this paper. CO2 emissions comparison of different RAP additions models and fuel types was analysed. The calculation model was presented for carbon emissions in most critical GHG generated AM production stage as new aggregates and RAP drying and heating.